Case––control study of the association between select HLA genes and anti-erythropoietin antibody-positive pure red-cell aplasia. (February 2008) - Fijal, Bonnie; Ricci, Deborah; Vercammen, Els; Palmer, Peter A; Fotiou, Fotis; Fife, Daniel; Lindholm, Anders; Broderick, Erin; Francke, Stephan; Wu, Xiaodong; Colaianne, James; Cohen, Nadine
Aims: Antibody (Ab)-positive pure red-cell aplasia (PRCA) is a very rare but serious adverse event associated with recombinant human erythropoietin treatment (4.1 reports per 100, 000  patient-years) in which patients produce antibodies to recombinant and endogenous erythropoietin, halting red blood cell production. In a previous case series, four Thai subjects with chronic kidney disease and Ab-positive PRCA were reported to have the HLA-DRB1*9 allele. To confirm a possible association of HLA-DRB1*9 and Ab-positive PRCA, we performed a pharmacogenomic analysis using subjects from an earlier case––control study of risk factors associated with Ab-positive PRCA, which had been performed using subjects from Europe or Canada. The primary goal of the analysis was to test the association between HLA-DRB1*9 and Ab-positive PRCA. A secondary goal was to perform an exploratory analysis in order to identify additional HLA alleles potentially associated with Ab-positive PRCA.Patients & Methods: Subjects were taken from a case––control study of Ab-positive PRCA in chronic kidney disease patients treated in Europe or Canada. Ab-positive PRCA cases (n  =  24) were matched to controls (n  =  81) by timing of treatment exposure and, when possible, by location.Results: The allele frequency of HLA-DRB1*9 was 12.5% in cases vs 1.2% in controls (p  =  0.002). The frequency of the HLA-DRB1*9 /other genotype was 25.0% in cases vs 2.5% in controls (p  =  0.004; OR:  10.8 [95% CI:  2.2––53.7]). Within the exploratory analysis, six additional HLA alleles ( HLA-A*25, HLA-B*53, HLA-C*12, HLA-DQB1*3, HLA-DQB1*6 and HLA-DRB1*4 ) were also found to be associated with Ab-positive PRCA.Conclusion: This study confirmed that HLA-DRB1*9 occurs at a significantly higher frequency in Ab-positive PRCA cases than in controls; however, within this sample set, carrying the *9 allele was neither necessary nor sufficient to cause Ab-positive PRCA.